Cultura da carpintaria naval: saberes etnomatemáticos aplicados à construção de embarcações artesanais no município de Marapanim - PA - MIRANDA, Kalilo Brasil (2021)
This study makes approaches ethnomathematics as an tool in the practice of naval carpentry in the borough of Marapanim-PA, a research site, whose general objective was: to investigate the origin of the mathematical knowledge used in the craft construction of vessels by naval carpenters, in the perspective of understanding If the knowledge used by carpenters comes from school knowledge or from Ethnomathematics, as well as identify the mathematical elements, mainly geometric, that make up the structure of the vessels and how these elements can assist in the teaching geometry. This research is of a qualitative nature, supported by bibliographic support. In the ethnographic study of this culture have been identified the presence of elements characteristic of geometry, as well as the know-how of the naval carpenters is related to the mathematics learned in school environment, however, during the visit to the shipyards it was verified that the knowledge used in carpentry naval come from Ethnomathematics, since they are generated and disseminated in the own culture, being perfected in the daily practice this craft and passed to the later generations. This study also aims at valuing the knowledge of other cultures based on Ethnomathematics and emphasizes the search for new discoveries for the teaching of Mathematics and emphasizes non-isolation this science with other areas of knowledge, but rather, allow mathematical communication with others sciences in an interdisciplinary way in search for new perspectives in the teaching of this one.